Comparative study On The ethical perceptions of contractors and designers in the China construction industry - Kang, Byung Gyoo; Long, Kaiwen; Zhang, Cheng; Li Hao, Jian (IOP Publishing, 2018)
Ethics is becoming one of the most important requirements for successful business in the 21st century. The construction industry cannot be exceptional from this trend. However construction ethics management requires different approaches from other industries, as the products of the industry are construction projects which are completely different from mass production. Contractors and designers are two major participants in construction projects. The roles and responsibilities of these two project stakeholders decisively influence all aspects of construction project. Practically ethical perceptions of contractors and designers are one of main aspects to be considered for the effective and efficient management of ethics for the construction industry. This research has investigated the ethical perceptions of contractors and designers in the China construction industry. A questionnaire survey which contains 15 ethical issues and 6 demographic factors has been conducted. 170 construction professionals from construction companies and consulting companies have been participated in this survey. These 15 ethical issues are ranked in terms of seriousness, frequency and importance for both contractors and designers as a single group to understand the overall perceptions in the industry. The analysis has also been conducted for contractors and designers respectively to make comparisons between them. The top three serious ethical issues in the industry are ‘Bribery and corruption’, ‘Failure to practice whistle-blowing’ and ‘Improper bidding practices’. Contractors and designers showed similar outcomes for the top five important ethical issues. But for the middle ranged ethical issues, they showed some differences. Further researches are required to identify the causes of the similarity and differences.